MASTER OF PUBLIC HEALTH FIELD EXPERIENCE REPORT: TRIHEALTH CORPORATE HEALTH - Morris, Joan Buchholz (My University, 2009)
In the fall of 2009, I completed my field experience requirement for the degree of Master of Public Health with an internship experience with TriHealth Corporate Health in Cincinnati, Ohio. Worksite health promotion has many health benefits for the employee as well as economic benefit for their employer and public value for the community as a whole. By bringing together the knowledge and expertise of the public health sector and the resources of the workplace, great accomplishments can be made in improving overall wellness of employees as well as the community through this new and innovative partnership. TriHealth Corporate Health’s core mission is to improve the health of the community they serve in the greater Cincinnati area. One avenue in which TriHealth works toward that goal is through worksite health promotion programs. These programs include health risk assessments, wellness screenings, health and wellness education, and health promotion programming. My experience working with TriHealth Corporate health was truly unique, exposed me to a realm of public health I had not yet experienced, and put the knowledge gained through my coursework into practical application.
Keywords: Worksite health promotion; TriHealth Corporate Health; Employee wellness; Health promotion programs; Wellness education; Health education; Home Economics (0386)